HUBUNGAN ANTARA GAYA HIDUP DAN STRES DENGAN KEJADIAN SINDROM DISPEPSIA PADA MAHASISWA ILMU KESEHATAN MASYARAKAT FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI: The Association between Lifestyle and Stress with Dyspepsia Syndrome in Students of the Public Health Sciences Study Program, Faculty of Medicine and Health Sciences of Jambi University - Vania Julia Permatasari Putri; M. Dody Izhar; Sitanggang, Hendra Dhermawan (Poltekes Kemenkes Tanjungpinang, 2022)
Dyspepsia is a set of symptoms such as pain and discomfort in the upper abdomen. The prevalence of dyspepsia among students ranges from 16.86-66.6%. This study aims to determine the association between lifestyle and stress with dyspepsia syndrome in students of the Public Health Sciences Study Program, Faculty of Medicine and Health Sciences of Jambi University. This study used an observational analytic study design with cross sectional approach. The population of this study was all active students of the Public Health Sciences Study Program, Faculty of Medicine and Health Sciences of Jambi University class of 2017, 2018 and 2019, as many as 954 students with a total sample of 366 respondents. The sampling technique was done using proportionate stratified random sampling. Data were collected using google form and analyzed univariately and bivariately using chi square. A total of 197 (53,8%) respondents reported having dyspepsia. Most of the respondents have a good diet (50,8%), non-smokers (95,9%) and stress (74,6%). The statical test results showed that there was association between stress and dyspepsia syndrome (p=0,005;PR=1,425;95%CI=1,094-1,857). There were no association between dietary habits (p=0,583;PR=1,065; 95%CI=0,881-1,288) and smoking (p=0,451;PR=1,251;95%CI=0,863-1,813) on dyspepsia syndrome. Lifestyle improvements are needed to reduce the risk of dyspepsia syndrome in students.